Green Entrepreneurial Orientation and Green Incremental Innovation: The Mediating Role of Supply Chain Learning - Syauqiyah Rouful Wahidah; Muhammad Ali Fikri; Poppy Laksita Rini (Journal of Economics, Social, and Humanities, 2025)
The concept of green entrepreneurial orientation combines aspects of entrepreneurship and environmental sustainability, supporting supply chain learning and enhancing the flow of information related to green incremental innovation. The research aims to analyze the effect of green entrepreneurial orientation on green incremental innovation with mediation of supply chain learning. The sample of this study consists of 85 hotel employees in Yogyakarta, Indonesia. Data processing was conducted using Structural Equation Model-Partial Least Square version 4.0. This study shows that green entrepreneurial orientation has a positive effect on green incremental innovation, green entrepreneurial orientation positively influences supply chain learning, supply chain learning positively impacts green incremental innovation, and green entrepreneurial orientation positively affects green incremental innovation with supply chain learning as a mediator.